2020
DOI: 10.3390/ijerph17082976
|View full text |Cite
|
Sign up to set email alerts
|

First Trimester Uterine Rupture: A Case Report and Literature Review

Abstract: The aim is to report a case of spontaneous uterine rupture in the first trimester of pregnancy and to review the literature on the topic. Methods: A literature search was performed using PubMed and Scopus. Relevant English articles were identified without any time or study limitations. The data were aggregated, and a summary statistic was calculated. Results: A 35-year-old gravida 5, para 2 was admitted at our department because of fainting and abdominal pain. The woman had a first-trimester twin pregnancy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 83 publications
1
10
0
1
Order By: Relevance
“…Indeed, our prompt intervention that involved immediate resuscitation and emergency laporatomy saved this woman's life. We noted similar sporadic reports of relatively similar cases by Gu'eye et al (12), Cecchini et al (13), as well as Halassy, Eastwood and Prezzato (14). Although we notice in all these cases that abdominal pain (no matter the severity) coupled with deranged fetal cardiac activity remain the two most important clinical manifestations.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, our prompt intervention that involved immediate resuscitation and emergency laporatomy saved this woman's life. We noted similar sporadic reports of relatively similar cases by Gu'eye et al (12), Cecchini et al (13), as well as Halassy, Eastwood and Prezzato (14). Although we notice in all these cases that abdominal pain (no matter the severity) coupled with deranged fetal cardiac activity remain the two most important clinical manifestations.…”
Section: Discussionsupporting
confidence: 89%
“…Rupture in this context is mainly correlated with a specific uterine abnormality, that is, a bicornuate uterus. According to the literature, bicornuate uteri show a particular vascular network between the 2 hemi-cavities, drawing the Greek letter y at the level of the midline [2,10]. One could hypothesize that this type of vascularization weakens the uterine wall, particularly at the level of the uterine fundus, where spontaneous rupture usually occurs.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review carried out by Fabiana Cecchini and allin January 2020 [2] summarized all cases of uterine rupture in the first trimester reported in the literature with a number of 76 case reports. She demonstrated that most first trimester uterine ruptures occur in a scarred uterus (69.74%) and that the three main surgeries associated with uterine wall disruption are cesarean section (67.92%), dilation and curettage (28.30%) and myomectomy (9.43%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the uterine scar rupture can be asymptomatic, which is a challenging situation for the obstetrician in terms of recognition and management. Uterine rupture can happen during labor or during the entire pregnancy (16)(17)(18).…”
Section: Risk Factor Rankingmentioning
confidence: 99%